Preterm birth, preeclampsia, gestational hypertension and offspring birth weight in women with active juvenile idiopathic arthritis and healthy controls - Götestam Skorpen, Carina; Lydersen, Stian; Salvesen, Kjell Å.; Wallenius, Marianne (Frontiers in Lupus, 2024)
Objectives: There is insufficient knowledge about pregnancy outcomes in women with juvenile idiopathic arthritis (JIA). Our objective was to explore a possible association of inflammatory active JIA and pregnancy outcomes, including preterm birth, preeclampsia, gestational hypertension, and offspring gestational weight.We linked data from the Norwegian nationwide observational register RevNatus with data from the Medical Birth Registry of Norway (MBRN) for the period 2010 to 2019. Singleton births in women with JIA (n= 181) included in RevNatus were cases. After excluding births in mothers with rheumatic inflammatory diseases , the remaining singleton births registered in MBRN , served as population controls (n = 575 798).Results: Preterm birth was more frequent in women with active JIA (17.6%) and of equivalent frequency in women with inactive JIA (3.1%), compared to population controls (4.9%). Preeclampsia had similar rates in women with JIA and population controls while gestational hypertension was more frequent in women with active JIA (7.2%) and inactive JIA (6.9%) compared to population controls (1.7%). Abnormal fetal growth occurred in similar rates in women with JIA and population controls.Having active JIA in pregnancy increased the risk for preterm birth (risk difference 12.7, 95% CI 4.7 to 25.3) and gestational hypertension (risk difference 6.2, 95% CI 1.4 to 16.8). There was no increased risk for preeclampsia or abnormal fetal growth compared to population controls.